2011
DOI: 10.1002/app.34309
|View full text |Cite
|
Sign up to set email alerts
|

Isoconversional and thermal methods of kinetic analysis of 2,4‐dihydroxybenzophenone copolymer resin

Abstract: A copolymer (2,4-DHBPOF) synthesized by the condensation of 2,4-dihydroxybenzophenone and oxamide with formaldehyde in the presence of acid catalyst with varying the molar proportions of the reacting monomer. Composition of the copolymer has been determined by elemental analysis. The copolymer has been characterized by UV-visible, FTIR, and 1 H NMR spectroscopy. The morphology of synthesized copolymer was studied by scanning electron microscopy (SEM). The activation energy (E a ) and thermal stability calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Since any spherical texture in the composites prepared in this study was not observed, it can be concluded that the -CH 2 -linkage plays a main role in the aniline sphere formation [20]. The extent of crystalline character depends on the acidic nature of the monomers [21].…”
Section: Xrd and Sem Analysismentioning
confidence: 69%
“…Since any spherical texture in the composites prepared in this study was not observed, it can be concluded that the -CH 2 -linkage plays a main role in the aniline sphere formation [20]. The extent of crystalline character depends on the acidic nature of the monomers [21].…”
Section: Xrd and Sem Analysismentioning
confidence: 69%
“…At 2.50 (δ) ppm signal is a result of the -CH 2 protons in the copolymer. The singlet at 3.41 (δ) ppm is caused by the proton of the N-CH 2 -N bridge [11][12]. The weak multiple signals that looked in the range of 7.21-8.10 (δ) ppm were all caused by the protons of the aromatic ring.…”
Section: Nmr Spectral Analysismentioning
confidence: 96%
“…The kinetic data processing was performed by applying the Freeman-Carroll method. [42][43] This method allows calculating the activation energy, pre-exponential factor and reaction order from a single TGA curve by Equation (1):…”
Section: Thermogravimetric Analysesmentioning
confidence: 99%